Investigating the Perception of Feedback in Software Development Teams: An Initial Study - Neves de Souza, Adriano; dos Santos, Fernanda; dos Santos, Lidvaldo; Helder Alvarenga Belém, Patrick; Thadeu Ferreira da Silva, Sirius; S. Vivacqua, Adriana; de Mello, Rafael (iSys - Journal of Information Systems, 2024)
The need for interaction between developers has increased over the decades, requiring efforts to promote effective communication. Feedback is an important tool that can be applied on different occasions, including informal conversations and planning meetings. However, an environment conducive to this practice is needed. We report a study on developers’ perception regarding the feedback practice and how it is related to the developers’ social identification with their teams. The results suggest that the perception of the feedback practice varies according to the occasion. We found evidence that feedback perception is correlated with participants’ identification with their teams.